The Effect of Green Human Resource Management and Work Motivation on Lecturer Performance with Organizational Commitment as Mediating Variable - Romanto, Kristian; Suprapto, Suprapto (Dinasti Publisher, 2025)
This study aims to examine the effect of Green Human Resource Management (GHRM) and work motivation on lecturer performance, with organizational commitment as a mediating variable, in the context of lecturers at Pelita Harapan University. A quantitative approach with a survey method was employed, involving 215 respondents selected through probability sampling. Data were analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) version 4.0. The study contributes to the field of human resource management in higher education by proposing a strategic empirical model supported by quantitative data, offering relevance for academic institutional performance improvement. This study uniquely integrates Green Human Resource Management (GHRM) and work motivation within a higher education context, highlighting organizational commitment as a mediator variable. The results reveal that GHRM and work motivation have a positive and significant effect on lecturer performance and organizational commitment. Moreover, organizational commitment significantly influences lecturer performance and fully mediates the relationship between both GHRM and work motivation with lecturer performance. These findings emphasize the importance of strengthening organizational commitment to optimize the impact of GHRM and work motivation on lecturer performance.